Cloning and mutagenesis of a herpesvirus genome as an infectious bacterial artificial chromosome - Messerle, Martin (The National Academy of Sciences of the USA, 1997)
A strategy for cloning and mutagenesis of an infectious herpesvirus genome is described. The mouse cytomegalovirus genome was cloned and maintained as a 230 kb bacterial artificial chromosome (BAC) in E. coli. Transfection of the BAC plasmid into eukaryotic cells led to a productive virus infection. The feasibility to introduce targeted mutations into the BAC cloned virus genome was shown by mutation of the immediate-early 1 gene and generation of a mutant virus. Thus, the complete construction of a mutant herpesvirus genome can now be carried out in a controlled manner prior to the reconstitution of infectious progeny. The described approach should be generally applicable to the mutagenesis of genomes of other large DNA viruses.